Promoting Students' Anticipatory Competency through the Rainwater Harvesting System Learning Project - Lestari, N. A.; Widodo, A.; Eliyawati, E. (Journal of Science Education Research, 2024)
In response to the pressing global challenges of climate change and water scarcity, the education sector seeks innovative approaches to nurture students' anticipatory competency. This study aims to investigate the improvement of students' anticipatory competency through rainwater harvesting system learning project. The method used in this research was Quasi-Experimental with Non-Equivalent Control Group Design research design. The sample used was class VII students consisting of a control class and an experimental class of 20 students each. Data were collected both before and after learning to assess students' anticipatory competence. The results showed that there was the significant different on Anticipatory competency in the experimental class. This means that rainwater harvesting system learning project effect on students' anticipatory competency The study implies positive impacts of utilizing the rainwater harvesting system learning project on students' anticipatory abilities to shape a future generation ready to tackle clean water and proper sanitation issues.